Respuesta :
Well you know that y=4x-9 for first one. So if that is what y equals then that means that you could replace y with 4x-9. If you did it I. first equation it would be:
4x-9 = 4x-9
That is pointless. But if you do it in second equation you get:
4x-9 = x-3
3x = 6
x=2
since x = 2 we can do:
y = x - 3
y = 2 - 3
y = -1
So solution is (2, -1)
4x-9 = 4x-9
That is pointless. But if you do it in second equation you get:
4x-9 = x-3
3x = 6
x=2
since x = 2 we can do:
y = x - 3
y = 2 - 3
y = -1
So solution is (2, -1)